Drug-Induced Hypersensitivity Syndrome Caused by Carbamazepine Used for the Treatment of Trigeminal Neuralgia - Yuko Ono; Tsuyoshi Shimo; Yoshinori Shirafuji; Toshihisa Hamada; Masanori Masui; Kyoichi Obata; Mayumi Yao; Koji Kishimoto; Akira Sasaki (Case Reports in Dentistry)
An 88-year-old man was diagnosed with trigeminal neuralgia, and treatment of carbamazepine 200 mg/day was initiated. About 6 weeks later, the patient developed a skin rash accompanied by fever. He was admitted to hospital and diagnosed with drug-induced hypersensitivity syndrome (DIHS) caused by carbamazepine. Oral carbamazepine treatment was stopped, but blood tests showed acute liver and acute renal failure. Drug-induced lymphocyte stimulation test (DLST) for carbamazepine, human herpes virus-6 (HHV-6) IgG, and CMV-HRP were negative. Oral prednisolone therapy was begun 18 days later. The titer of HHV-6 IgG antibodies was then detected (640 times). Following treatment, liver and renal function improved and the erythema disappeared.